"Frank Prewett, A Canadian Georgian Poet." - Precosky, Donald (Studies in Canadian Literature, 1979)
Frank Prewett’s gloomy attitudes toward nature, Canada, and life in general make him an interesting contrast to contemporaries such as Arthur Bourinot and W.W.E. Ross.